Homozygous deletion of the DPY19L2 gene as a major genetic cause of globozoospermia: a case report from Senegal - Thierno Abdoulaye Diallo; Abdou Diop; Boubacar Faye; Babacar Ndiaye; Mama Sy; Libasse Niang; Micheline Misrahi; Rena Derwiche; Chantal Mahou; Natacha Gaitch; Brigitte Martinez; Florence Hourriez; et al. (Egyptian Journal of Medical Human Genetics)
Abstract Background Globozoospermia is a rare but serious teratozoospermia, characterised by ejaculates consisting of entirely of round-headed spermatozoa without acrosomes or, in the case of partial globozoospermia, containing a variable proportion (20 to 90%) of spermatozoa without acrosomes. Men with total globozoospermia are infertile, and even the use of intracytoplasmic sperm injection (ICSI) has been associated with disappointing success rates. Case presentation The aim of this study was to determine genetic causes of globozoospermia in two patients referred to medical biology laboratory at Pasteur Institute of Dakar. After spermogram, two whole blood samples on EDTA tubes were sent for genetic testing. Molecular analysis by NGS sequencing of 14 genes responsible for teratozoospermia revealed a homozygous deletion of entire coding region of the DPY19L2 gene in our two unrelated patients. Conclusion This study confirmed need to complement spermogram with genetic testing in order to confirm diagnosis and to advice on the appropriate management of patients, regardless of phenotype on spermogram.